Evaluating a sexual violence primary prevention program at an Australian University: a realist protocol comprising a cluster non-randomized controlled trial and realist interviews - Innocent Mwatsiya; Jessica Ison; Kerryn O’Rourke; Kirsty Forsdike; Sarah Vrankovich; Jacqueline Kuruppu; Freda Haylett; Jacqui Theobald; Gabriel Caluzzi; Xia Li; Adam Bourne; Nicola Henry; et al. (BMC Public Health, 2026)
Abstract Background Sexual violence is highly prevalent in university settings, yet there remains limited evidence on what prevention interventions work, for whom, and under what conditions. This article outlines the protocol for a mixed method realist evaluation of an Australian sexual violence prevention program for university students. Methods/design This study is designed to test and refine eight initial program theories developed with key informants. Four theories hypothesise changes in participant sexual violence knowledge, attitudes and behaviours. Outcomes of these will be tested in a two-arm parallel cluster non-randomized controlled trial. Realist interviews with program participants, university staff and facilitators will also test these outcomes, as well as their hypothesised mechanisms and contexts. Three initial program theories about implementation will be tested in the realist interviews only complemented with the Reach, Effectiveness, Adoption, Implementation, and Maintenance (REAIM) framework. Study arms The trial will be conducted with university students and staff across nine residential colleges at one Australian university in 2026. The residential colleges will be the unit of selection for assignment into clusters. Nine clusters will be allocated to either intervention ( n = 5) or control arms ( n = 4). Total student sample size n = 191. The intervention group will receive the Consent and Relationship Education (CaRE) program, a 4-session group-based intervention that aims to educate participants on healthy relationships and the prevention of sexual violence. Primary outcome: sexual violence knowledge. Secondary outcomes: sexual violence attitudes, behaviours (perpetration and victimization). Students in all clusters will complete surveys at baseline, immediate-post, 3-months-post and 6-months-post the intervention. Discussion To our knowledge, this study will comprise the first published trial and the first realist evaluation of a sexual violence primary prevention program delivered in an Australian university context. The use of realist methodology and mixed methods will advance the field’s understanding of not only “what works” to prevent sexual violence, but also how, when and for whom it works (or not). Trial registration This study has been approved by the La Trobe University Human Research Ethics Committee (approval number HEC25176). The trial has also been registered with the Australian New Zealand Clinical Trials Registry (ACTRN12625000602426p).